Tobacco use in Northern India-Part 1: The detailed habit - Sandeep Kumar; Varsha Dwivedi; Upendra Pandey; Nidhi Bala; Sheela Vasandani; Kamlesh Singh; Kishore Chaudhry (Elsevier, 2011)
ABSTRACT: Background: The finite details of tobacco consumption practices in north Indian population are hitherto not well described. This study depicts the modes of tobacco use, their relative frequency, demographic and psychosocial determinants. Materials and Methods: Random stratified sampling from the list of blocks, villages and urban localities was done. The study was community-based house-to-house survey using interview schedule. Results: There were 1607 tobacco users: 1399 male and 208 female; 1195 urban and 412 rural. Single mode of tobacco use was reported by 769 (47.85%). Chewing tobacco was prevalent in 511 (31.80%), smoking in 258 (16.55%) subjects and majority 838 (52.15%) had consistent multiple habit of smoking and chewing. Of the 10 preparations of tobacco use, the 'top 5' ranked as tobacco-betel, gutka, cigarette, bidi and khaini. Gutka consumption was significantly higher between age group of 25 years and 55 years (χ2 = 17.2; P<0.000). Majority of users, 576 (35.84%), started tobacco before 25 years of age and about a fifth, 439 (27.32%) before 18 years. Men significantly used tobacco more than women (χ2 = 73.2; P<0.000). Women (χ2 = 73.2; P<0.000) preferred smokeless tobacco and perceived social barrier for smoking. Conclusion: Multiple or overlapping tobacco practices and other substances abuse were documented in Lucknow, the capital city of the most populous state Uttar Pradesh where chewing tobacco was the commonest as opposed to smoking.